The coherent organization of dynamic visual images - Lappin, Joseph S.; Bell, Herbert H. (Frontiers in Computer Science, 2023)
Biological vision relies on the intrinsic spatiotemporal structure of a continuously flowing image stream. We review converging psychophysical and physiological evidence about the structure and precision of the perceived spatiotemporal organization of dynamic images. Visual acuity, temporal resolution, and contrast sensitivity have been found to involve (a) motion-produced increases in image contrast, (b) coherent phase relations among temporally varying retinal signals, and (c) physiological preservation of spatiotemporal structure from retina to cortex. Moreover, psychophysical theory and evidence show that the spatiotemporal structure of dynamic retinal images carries precise information for perceiving surfaces and motions—consistent with the corresponding differential structures of spatiotemporal images and environmental surfaces.